PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN BERBASIS ARTIFICIAL INTELLIGENCE (AI) BAGI GURU PENJAS - Marsuki, Marsuki; Torano, Fazryani Mazita; Hidayah, Hidayah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This training is entitled “Training on Making Artificial Intelligence (AI)-Based Learning Videos for Physical Education Teachers” and is motivated by the digital literacy gap among physical education teachers in the digital 4.0 era, where 40% of teachers have a basic understanding of AI but almost none of them have implemented it in their teaching, while Generation Z and Alpha students need innovative and interactive learning approaches in line with technological developments. The objective of the training is to improve the digital competence of physical education teachers in creating AI-based learning videos, effectively integrating AI technology, and creating interactive learning media to improve the quality of physical education learning. The training was conducted over two days with a theoretical and practical approach by a team from Cenderawasih University, covering four main topics: an introduction to AI in learning, AI tools and applications (Pictory, Lumen5, Synthesia, Descript), steps for making videos, and editing using Kapwing with intensive guidance. The training results showed that 78% of teachers successfully produced at least 2 quality learning videos, 85% of teachers felt more confident in using AI technology, a sustainable learning community was formed with 24 active teachers collaborating, and an AI-based motion analysis system with a response time of 1.8 seconds and 95% cross-device compatibility. The training outcomes included an 83% increase in student engagement, a 12.5% increase in learning outcomes, a transformation of learning from a traditional paradigm to modern adaptive learning, the availability of digital resources in the form of modules, tutorials, and AI application guides, and scientific publications in Sinta-level community service journals. ABSTRAKPelatihan ini berjudul